Utilizing VR Visual Novels Incorporating Social Stories for Learning in Children with Autism Spectrum Disorder: A Systematic Literature Review - Katerina Atsalaki; Ioannis Kazanidis (Multimodal Technologies and Interaction)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition that impacts social, communication, and emotional skills, presenting significant challenges in learning and social interaction. Traditional teaching approaches often fail to engage children with ASD, highlighting the need for innovative solutions. This study investigates the potential of virtual reality (VR) visual novels, incorporating social stories, as a tool to enhance social skills in children with ASD Level 1. Through a comprehensive literature review, the research evaluates VR environments that blend the interactive, choice-based structure of visual novels with immersive social narratives. Key aspects such as empathy, communication, and emotional regulation are analyzed to assess whether VR-based social stories provide better learning outcomes compared to conventional 2D methods. The findings aim to inform about the application of VR technologies in educational interventions, demonstrating how immersive learning experiences can promote essential social competencies in children with ASD.